Human Resources Implementation Using the McKinsey 7S Method for Business Startup: Duck Nugget Frozen Food - Ryan Perdana Putra; Tantri Yanuar Rahmat Syah; Semerdanta Pusaka; Rhian Indradewa (Journal of Multidisciplinary Academic, 2019)
The purpose of Nugget Duck-Duckan business plan is a company manufactures processed "nugget" meat derived from selected duck meat with hygienic quality standards. In order to produce quality and safe duck nuggets, the consumption duck nugget meat have provide to customer demand also for customer satisfaction. The basic analysis and operational thinking of Nugget Duck-Duckan business is carried out using stages or HR models consisting of strategy, system, skill, style, staffing, structure and share vision. Strategic location is needed to support this business over PT. Befindo Food located at Jl. Raya Narogong Blok Pv. Timur RT.3 / RW.1, Ciketing Udik, Bantargebang, Bekasi, West Java 17153. PT. Befindo Food have Duck-Duckan Duck Nugget product and produces processed "meat nuggets" from duck meat. In this study we analyze the business opportunity using questioner form over PT. Befindo Food to obtain success factor ratio. Here, the McKinsey 7s Framework was proposed to obtain sucess factor from correstpondent. This framework also used to analyze the internal aspects of a company's organization with 7 main elements such as Strategy, Systems, Skills, Style, Staff, Structure and Share values